DOCK4 Regulation of Rho GTPases Mediates Pulmonary Vascular Barrier Function. Issue 7 (28th April 2022) - Yazbeck, Pascal; Cullere, Xavier; Bennett, Paul; Yajnik, Vijay; Wang, Huan; Kawada, Kenji; Davis, Vanessa M.; Parikh, Asit; Kuo, Andrew; Mysore, Vijayashree; Hla, Timothy; Milstone, David S.; et al.
Abstract : Background: The vascular endothelium maintains tissue-fluid homeostasis by controlling the passage of large molecules and fluid between the blood and interstitial space. The interaction of catenins and the actin cytoskeleton with VE-cadherin (vascular endothelial cadherin) is the primary mechanism for stabilizing AJs (adherens junctions), thereby preventing lung vascular barrier disruption. Members of the Rho (Ras homology) family of GTPases and conventional GEFs (guanine exchange factors) of these GTPases have been demonstrated to play important roles in regulating endothelial permeability. Here, we evaluated the role of DOCK4 (dedicator of cytokinesis 4)—an unconventional Rho family GTPase GEF in vascular function. Methods: We generated mice deficient in DOCK4‚ used DOCK4 silencing and reconstitution approaches in human pulmonary artery endothelial cells‚ used assays to evaluate protein localization, endothelial cell permeability, and small GTPase activation. Results: Our data show that DOCK4-deficient mice are viable. However, these mice have hemorrhage selectively in the lung, incomplete smooth muscle cell coverage in pulmonary vessels, increased basal microvascular permeability, and impaired response to S1P (sphingosine-1-phosphate)–induced reversal of thrombin-induced permeability. Consistent with this, DOCK4 rapidly translocates to the cell periphery and associates with the detergent-insoluble fraction following S1P treatment, and its absence prevents S1P-induced Rac-1 activation and enhancement of barrier function. Moreover, DOCK4-silenced pulmonary artery endothelial cells exhibit enhanced basal permeability in vitro that is associated with enhanced Rho GTPase activation. Conclusions: Our findings indicate that DOCK4 maintains AJs necessary for lung vascular barrier function by establishing the normal balance between RhoA (Ras homolog family member A) and Rac-1–mediated actin cytoskeleton remodeling, a previously unappreciated function for the atypical GEF family of molecules. Our studies also identify S1P as a potential upstream regulator of DOCK4 activity.